BEYOND HARMONIZATION: CONFLICT RESOLUTION AS A LEGAL BRIDGE OF INDONESIAN ISLAMIC FAMILY LAW REFORM IN KOMPILASI HUKUM ISLAM - Sembodo, Cipto; Arifin, Zainul; Rahayu, Supriati Hardi; Syafi’i Rahman, Ahmad; Mochammad Sahid, Mualimin (Indonesian Journal of Shariah and Justice, 2025)
This article examines conflict resolution patterns between Islamic law and customary law in the formation of Compilation of Islamic Law (KHI) in Indonesia. KHI constitutes a legal entity and a genuinely reformative bridge within legal pluralism, not mere an object of harmonization, and affirms that such conflicts are not anomalous. Employing a juridical-normative approach and conceptual analysis, the study traces how KHI represents the state’s ijtihad in responding to tensions among sharia norms, customary practices, and Indonesian Muslim society. The findings demonstrate three principal patterns of conflict resolution: (1) normative compromise between classical fiqh and customary practices, giving rise to the distinctly Indonesian concept of wasiat wajibah (mandatory bequest); (2) the adoption of customary institutions aligned with the principles of Islamic law, as the marital joint property showed; (3) adjusting customary norms within a sharia framework, exemplified by the concept of substitute heirs. These patterns underscore methodological and reflective nature of conflict resolution within KHI. KHI emerges as a model of active and productive normative conflict resolution within Indonesia’s legal pluralism. This constitutes a theoretical contribution to contemporary Islamic legal scholarship while proposing a policy-oriented direction for a more inclusive, contextual, and maqāṣid al- sharīʿah-oriented reform of the KHI.